Keanekaragaman dan Kepadatan Semut (Hymenoptera, Formicidae) di Lahan Gambut Alami - Yulminarti Yulminarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of open peatland areas on ant diversity. This research method uses a quantitative descriptive approach by collecting ant samples using the pitfall traps method. The results showed that the total number of ant species found in this study was 129. In natural peat forests, 113 species were found from 3660 individuals and in open peatland found 49 species from 5976 individuals. The diversity index is 2.38 in natural peat forests and the diversity index is 1.91 in open peatland. In conclusion, the number of ant species decreases with the open area. Keywords: Peatlands, Oil Palm, Ants